Get real - Westlake, Donald E. (Westlake, Donald E. Dortmunder series., 2009)
When a TV producer convinces John Dortmunder and his merry gang to do a reality show that captures their next score, Dortmunder hatches an ingenious plan to outwit viewers glued to their television sets and end the shoot with money in his pockets.